THE RELATIONSHIP BETWEEN QUALITY OF LIFE AND SUCCESSFUL AGING - Reini Astuti; Tri Wahyuningsih; Ratna Wulan Hadian (Jurnal Kesehatan Budi Luhur)
The elderly population is increasing rapidly worldwide, including in Indonesia, leading to significant health, social, and economic implications. The aging process often leads to physical, psychological, and social changes that can negatively affect quality of life.Thus, ensuring a high quality of life is crucial for achieving successful aging. This study aimed to analyze the relationship between the quality of life and successful aging among elderly individuals in Cimahi City. A cross-sectional study was conducted with 128 elderly participants, selected proportionally WHOQOL-BREF and SAS should be briefly explained with full names in parentheses when first mentioned for clarity to readers unfamiliar with them. Was used to assess quality of life, while the Successful Aging Scale (SAS) was employed to evaluate successful aging. Bivariate analysis was performed using the Chi-square test at a significance level of p<0.05. A significant relationship was found between successful aging and the physical (p=0.003), psychological (p=0.000), and environmental (p=0.002) domains of quality of life. However, no significant association was observed in the social domain (p=0.114). The results suggest that physical health, psychological well-being, and environmental support are key factors contributing to successful aging. Social relationships, though important, did not show a statistically significant impact in this study. Health interventions and policies aimed at promoting successful aging should prioritize improving the quality of life for the elderly, particularly by enhancing physical and mental health and ensuring a supportive and secure living environment.